Mapping of Bernal and non-Bernal stacking domains in bilayer graphene using infrared nanoscopy. Issue 12 (13th March 2017) - Jeong, Gyouil; Choi, Boogeon; Kim, Deok-Soo; Ahn, Seongjin; Park, Baekwon; Kang, Jin Hyoun; Min, Hongki; Hong, Byung Hee; Kim, Zee Hwan
Abstract : We demonstrate that infrared nanoscopy can visualize Bernal and non-Bernal stacking domains of bilayer graphene, based on the stacking-specific inter- and intra-band optical conductivities. Abstract : Bilayer graphene (BLG) shows great potential as a new material for opto-electronic devices because its bandgap can be controlled by varying the stacking orders, as well as by applying an external electric field. An imaging technique that can visualize and characterize various stacking domains in BLG may greatly help in fully utilizing such properties of BLG. Here we demonstrate that infrared (IR) scattering-type scanning near-field optical microscopy (sSNOM) can visualize Bernal and non-Bernal stacking domains of BLG, based on the stacking-specific inter- and intra-band optical conductivities. The method enables nanometric mapping of stacking domains in BLG on dielectric substrates, augmenting current limitations of Raman spectroscopy and electron microscopy techniques for the structural characterization of BLG.